2022
DOI: 10.1093/mr/roac074
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in familial Mediterranean fever: Clinical course and complications related to primary disease

Abstract: Objective Aim of the study is to evaluate the impact of Familial Mediterranean Fever (FMF) features on clinical course and outcomes of Coronavirus disease-19 (COVID-19) and clinical course of FMF after COVID-19. Methods Consecutive FMF patients with COVID-19 were enrolled from three referral hospitals. Clinical features of FMF and detailed COVID-19 information were obtained from patient interviews and medical records. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In previous studies in COVID-19 patients with FMF, FMF characteristics were not associated with worse outcomes in nonpregnant patients. 39 In this study, 4 pregnant women with FMF were admitted to the ICU, and 1 of them died. In previous studies, patients with selective IgA deficiency 40 and Factor V Leiden thrombophilia 41 had a higher risk of severe COVID-19 infection.…”
Section: Discussionmentioning
confidence: 92%
“…In previous studies in COVID-19 patients with FMF, FMF characteristics were not associated with worse outcomes in nonpregnant patients. 39 In this study, 4 pregnant women with FMF were admitted to the ICU, and 1 of them died. In previous studies, patients with selective IgA deficiency 40 and Factor V Leiden thrombophilia 41 had a higher risk of severe COVID-19 infection.…”
Section: Discussionmentioning
confidence: 92%
“…The frequency and severity of SARS-CoV-2 infection in FMF are intriguing. Gunendi et al [9] and Guler et al [15] stated in their studies that FMFrelated characteristics were not associated with poor COVID-19 outcomes and were not a risk factor.…”
Section: Discussionmentioning
confidence: 97%
“…Guler et al stated that not using colchicine is a risk factor for hospitalization and oxygen support [15]. Bourguiba et al found similar incidence rates of COVID-19 in FMF patients (8%) and the general population (11%) in a French endemic region [16].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported worsening FMF symptoms after acute COVID-19 illness in 33% of patients with FMF, 7 perhaps through additive inflammasome dysregulation, which can occur both in patients with FMF 8 and in patients with acute COVID infection. 9 Given the potential for effective therapy, clinicians should obtain a thorough fever history and consider genetic testing for autoinflammatory diseases in children experiencing post-COVID recurrent fevers.…”
mentioning
confidence: 99%